From Canaan to Egypt (Gn 12:10–20): Abraham"s sojourn and its ethical dilemma for migrants in socio-economic circumstances - Boloje, Blessing O. (HTS teologiese studies, 2024)
Migration of people, whether legal or not, is no doubt one of the universe’s enigmas. As a subject that seeks the engagement of interdisciplinary approaches, the biblical text is not in shortage of references to the movement and resettlement of individuals across different narratives and literary forms. Numerous references to ‘sojourners’, ‘migrants’, and the intricacies and reactions that migration generates are found in several portions of the Pentateuch. By employing a narrative methodology and a hermeneutic of ethical deduction as interpretive approach, this article holds that, the patriarchal narrative of Genesis 12:10–20, is fittingly, a narrative of migration that raises several ethical challenges that are profoundly relevant to migrants in socio-economic situations. Abraham’s vulnerable position as a migrant under socio-economic circumstances to Egypt created fear in him and presented him moral dilemmas in which inequalities created by wealth and poverty posed dangers of losing faith. Many individuals and families are faced with similar circumstances today, being caught up in webs of difficult considerations and forced to make unpleasant decisions.Contribution: This article employs a narrative reading of Abraham’s sojourn in Genesis 12:10–20 in an attempt to bring together biblical, literary and theological discourses into dialogue with ethics and migration. The article serves as a viable starting point for discussions about the ethical considerations faced by migrants in socio-economic situations, and how principles of honesty, empathy and responsible decision-making can guide their actions.